Easy chemistry step-by-step master high-frequency concepts for chemistry proficiency--fast! - DeWane, Marian L. (McGraw-Hill Education, 2014)
Easy Chemistry Step-by-Step is based on the idea that the quickest route to learning this subject isbuilding a solid foundation in the basics. You won't find a lot of pointless discussion; instead, you get an original, step-by-step approach to mastering chemistry, with important concepts linked together by clear explanations, appropriate exercises, and helpful answers.--Publisher's description.